Efektivitas Pelaksanaan Prosedur Perjalanan Dinas di PT. Hurip Utama Cikampek - Dina Nurlia Fajar; Sungkono S (Yayasan Daarul Huda Kruengmane, 2023)
The effectiveness of the implementation of business travel procedures is very important to ensure that every business trip undertaken by employees can be carried out efficiently and on target. This involves several aspects that need attention, including submitting travel requests, determining routes and schedules, using budgets, and reporting trip results. Effective business travel procedures can help companies or organizations save on travel costs, reduce the risk of errors or mistakes, and increase the productivity of employees who travel on business. On the other hand, ineffective business travel procedures can lead to financial loss, employee dissatisfaction and legal problems. To increase the effectiveness of the implementation of official travel procedures, companies or organizations must have a clear and integrated system to manage each stage of the business travel process. This can include using applications or software that can facilitate the submission of travel requests, determining routes and schedules, managing budgets, and reporting trip results. In addition, the company or organization must also have clear operational standards to regulate every aspect related to official travel, including applicable rules and regulations, time and budget limits, and actions to be taken if problems occur during the trip. Thus, the effectiveness of implementing business travel procedures can assist companies or organizations in achieving their business goals, increasing efficiency, and improving the performance of employees who travel on business.